Low-Complexity Design of Frequency-Hopping Codes for MIMO Radar for Arbitrary Doppler. (7th October 2010) - S. S., Badrinath Badrinath; Srinivas Srinivas, Anand Anand; Reddy Reddy, V. U. V. U.
Abstract : There has been a recent interest in the application of Multiple-Input Multiple-Output (MIMO) communication concepts to radars. Recent literature discusses optimization of orthogonal frequency-hopping waveforms for MIMO radars, based on a newly formulated MIMO ambiguity function. Existing literature however makes the assumption of small target Doppler. We first extend the scope of this ambiguity function to large values of target Doppler. We introduce the concept of hit-matrix in the MIMO context, which is based on the hit-array, which has been used extensively in the context of frequency-hopping waveforms for phased-array radars. We then propose new methods to obtain near optimal waveforms in both the large and small Doppler scenarios. Under the large Doppler scenario, we propose the use of a cost function based on the hit-matrix which offers a significantly lower computational complexity as compared to an ambiguity based cost function, with no loss in code performance. In the small Doppler scenario, we present an algorithm for directly designing the waveform from certain properties of the ambiguity function in conjunction with the hit-matrix. Finally, we introduce "weighted optimization" wherein we mask the cost function used in the heuristic search algorithm to reflect the properties of the required ambiguity function.